Perselisihan Paulus dan Barnabas: Tanda Gereja yang Hidup dan Berpikir - Ira Suwitomo Putri; Asih Rachmani Endang Sumiwi (Sekolah Tinggi Teologi Berita Hidup, 2026)
Paul and Barnabas were central figures in the spread of the gospel in the early church, but their partnership was marred by a sharp dispute over John Mark's participation in the second missionary journey. This article aims to revisit the conflict from a progressive perspective, arguing that it is not a failure of ministry, but a reflection of a church that is alive and has the ability to think critically for the sake of common progress. This study uses a historical-descriptive analysis method with an exegetical approach to trace the roots of the conflict and the reasons behind the decisions of the two figures. The analysis shows that the tensions that occurred were rooted in differences in strategic considerations: Paul emphasized full commitment and mission effectiveness, while Barnabas emphasized the value of grace, forgiveness, and a second chance for individual recovery. The separation that occurred eventually became a